A protocol for a systematic review of effective home support to people with dementia and their carers: components and impacts. (28th July 2015) - Clarkson, Paul; Giebel, Clarissa M.; Larbey, Matthew; Roe, Brenda; Challis, David; Hughes, Jane; Jolley, David; Poland, Fiona; Russell, Ian; ,
Abstract: Aim: To review the evidence for home support approaches directed at tertiary prevention; ameliorating difficulties and enhancing well‐being. Background: With population ageing dementia represents a significant care challenge with 60% of people with dementia living at home. However, little is known about existing forms of home support and their relative effectiveness. Design: A two‐stage design: First, an overview of systematic reviews of psychosocial interventions for dementia to identify their components; second, a systematic review of the effectiveness of home support interventions to older people with dementia/their carers. Methods: We will search electronic databases using specific search terms with additional searches of other known studies. Data will be extracted by two reviewers according to pre‐determined categories. An initial synthesis will elicit components of interventions from stage 1 and operationalize them in terms of specific techniques. These will then be used in synthesis of data in stage 2, to determine the extent to which each home support intervention relies on these components and distill evidence concerning outcomes. Studies from stage 2 are expected to be methodologically diverse; if so, a narrative approach to synthesis will be taken. Study findings will be explored with Patient, Public and Carer Involvement groups. Discussion: The review seeks to develop a theory of home support: how and why interventions may work; in what contexts; and for whom. We will identify effective home support approaches, informing policy‐makers and establishing how they might be experienced by people with dementia and their carers.